Sleep disorders in women : a guide to practical management - Viola-Saltzman, Mari; Attarian, Hrayr P. (Current Clinical Neurology, 2013)
In Sleep Disorders in Women: A Guide to Practical Management, 2nd Edition, a multidisciplinary panel of eminent researchers and practicing clinicians comprehensively updates the multifaceted aspects of sleep disorders in women at different stages of life, illuminating the unique impact that each reproductive and endocrine stage has on both normal sleep and sleep disorders. This title not only introduces primary care physicians and health care providers to the discipline of sleep disorders in women, it also will appeal to a broader set of specialists as it summarizes the latest, cutting-edge research and presents it in a succinct and clinically relevant manner.  The goal of this book is to help physicians recognize the symptom patterns of sleep disorders in their female patients, guide them in diagnosing and treating these patients in a timely fashion, and help in the elimination of gender bias in sleep medicine research and care.   An invaluable addition to the literature,  Sleep Disorders in Women: A Guide to Practical Management, 2nd Edition again fills an important niche by being an accessible, comprehensive,  multidisciplinary review on sleep disorders in women.